Financing Process Analysis of Bank Nagari Syariah and BPRS in West Sumatra: Precautionary Principle Implementation - Yenti, Fitri; Wahyuni, Elmiliyani; Shabri, Husni (Al-bank: Journal of Islamic Banking and Finance, 2025)
This study aims to analyze the financing implementation process at Bank Nagari Syariah and Sharia Rural Banks (BPRS) in West Sumatra, focusing on the application of the precautionary principle. This research employs a descriptive qualitative method, with data collected through in-depth interviews, document analysis, and direct observation of eight BPRS: PT BPRS Mentari Saiyo, PT BPRS Haji Miskin, PT BPRS Carana Kiat Andalas Bukittinggi, PT BPRS Ampek Angkek Canduang, PT BPRS Almakmur Payakumbuh, PT BPRS Sungai Puar Syariah, PT BPRS Barakah Nawaitul Ikhlas Solok, and PT BPRS Gajah Nan Tongga Sawah Lunto. The data were analyzed thematically, focusing on the implementation of the 6C and 5C assessment methods. The findings reveal that Bank Nagari Syariah and BPRS consistently apply the precautionary principle to mitigate the risk of default. This study implies the need to strengthen risk assessment systems based on sharia principles to improve financing asset quality and enhance customer trust in sharia banking